Comparative Analysis of Economic Diplomacy of The PRC and The ROK to DR Congo - Mulyaman, Darynaufal; Ismail, Achmad; Setiawan, Theofilus Jose (Department of International Relations, Universitas Mulawarman, 2025)
The purpose of this study is to analyze comparative economic diplomacy carried out by the PRC and the ROK to DR Congo as an effort to safeguard natural resources (cobalt and copper), competition, and the impact on the SDGs agenda using International Relation’s Liberalism Theory and secondary data. PRC and the ROK need to secure cobalt and copper so that their electric vehicle industry can continue to compete in the world electric vehicle market. DR Congo is the world's largest producer of cobalt and the fourth largest copper producer in the world. DR Congo's GDP is ranked 45th out of 53 African countries. Thus, DR Congo must be able to build the country's infrastructure so that its GDP can increase. PRC and the ROK, thirsty for cobalt and copper for their electric vehicle industries, are moving closer to DR Congo to secure its cobalt and copper. The economic diplomacy carried out by the PRC is a resource for infrastructure while the ROK is based on the principle of mutual benefits. Thus, PRC and the ROK get resources (cobalt and copper) and DR Congo gets the country’s development which is following several SDGs agendas. This paper answers that the economic diplomacy carried out by the PRC and the ROK to DR Congo is an attempt to secure cobalt and copper, creates a competitive environment between PRC and the ROK, and also has an impact on the SDGs in DR Congo.